We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
157
1
avatar+630 

The expression \(x^2 - 16x + 60\) can be written in the form \((x - a)(x - b)\), where \(a\) and  \(b\)  are both nonnegative integers and \(a > b\). What is the value of \(3b - a\)?

 Sep 14, 2018
 #1
avatar
+2

Factor the following:
x^2 - 16 x + 60

The factors of 60 that sum to -16 are -6 and -10. So, x^2 - 16 x + 60 = (x - 6) (x - 10):
(x - 10)(x - 6)

a=10   and   b=6

3b - a =18 - 10=8

 Sep 14, 2018

7 Online Users

avatar